MANFAAT AKTIVASI FLY ASH BATU BARA DENGAN VARIASI KONSENTRASI NAOH SEBAGAI ADSORBEN - Khuzaimah, Siti (Jurnal Inovasi Daerah, 2024)
Water is one of the most important natural resources for human life. However, there are some problems that cause water to get polluted and not be used properly, one of which is the liquid waste of the hydrocarbon industry. Fly ash is a residue from coal combustion. Fly ash can be used as an adsorbent to reduce the content of hazardous fluid waste that could threaten human life. The study aims to find out the best NaOH concentration ratio between 1 M and 3 M added to activate fly ash against COD decrease, BOD, TSS, pH, and color change in Kutawaru Cilacap battery waste. The study passes through several stages, namely the first phase of activation of fly ash with NaOH at concentration ratios of 1M and 3M with a ratio of 1:5 for 3 hours. Then, in the adsorption process, the activated fly ash is mixed with battery liquid waste. The final phase is the testing of batik waste at the DLH Cilacap. The results obtained are at the concentration of 1M NaOH because it can reduce COD, BOD, and TSS up to 76%. With the result of COD of 3286 mg/L, BOD of 4921 mg/L, and TSS of 115 mg/L, whereas the results of concentration 3M, with COD of 3615 mg/L, COD 5397 mg/L, and TSS of 36 mg/L, PH for both these concentrations of 8 and the change in color of waste batik that remains black concentrated.